The Role of the Ilizarov Ring External Fixator in the Management of Tibial Fractures with Impending/Incomplete Compartment Syndrome - Bhowmick, Kaushik; Gunasekaran, Chandrasekaran; Kandoth, Jacob J.; Ramasamy, Boopalan; Jepegnanam, Thilak S. (Revista Brasileira de Ortopedia, 2021)
Objective The management of tibia fractures complicated by compartment syndrome affects the treatment and functional outcome of patients due to the complications associated with fasciotomy. The purpose of the present study is to differentiate impending/incomplete compartment syndrome (ICS) from established acute compartment syndrome (ACS) in tibial fractures, and to assess the outcome of the fixation of the Ilizarov apparatus in patients with these fractures presenting with ICS, who were not submitted to fasciotomy.Methods After the establishment of the inclusion and exclusion criteria, 19 patients were included in the study from January 2007 to December 2017. All patients were male, with an average age of 42.3 ± 11.38 years. All of these patients were managed with Ilizarov ring fixation as per the medical and surgical protocol established in the present study.Results The average follow-up obtained for our 18 patients was of 47 ± 41.5 months, with one patient being lost to follow-up. The average time for ring application was of 3.7 ± 1.7 days. In total, 3 (16.7%) of these patients had nonunion. There were no soft-tissue or neurovascular complications in the immediate postoperative period. All of the patients eventually united and were independently mobile without any sequelae of compartment syndrome.Conclusion The Ilizarov ring external fixator can be used in the management of tibial fractures with ICS, avoiding fasciotomy with its various complications of infection and nonunion, resulting in fewer surgeries and faster rehabilitation. Surgeons should carefully differentiate ACS and ICS in these patients, as the clinical and functional results vary significantly. Unnecessary fasciotomies should be avoided.
Keywords: Ilizarov technique; tibial fractures; compartment syndromes